Pengaruh konsentrasi ozon terhadap cemaran mikroba pada air minum dalam kemasan - Sri Agustini; Rienoviar . (Balai Riset dan Standardisasi Industri Palembang, 2011)
A study on the effect of ozone concentration on the microbial contamination on the bottled drinking water has been done. The objective was to get the optimum concentration of ozone in disinfection in the bottled drinking water production. The treatment was concentrating ozone in mixing tank 0.1 ppm; 0.2 ppm; 0.3 ppm; 0.4 ppm; 0.5 ppm and 0.6 ppm. Experiment were done for two bottled drinking water producers in Palembang, and Bengkulu. Treated Samples were sent to accredited laboratory to be tested for Total plate count, coliform and salmonella by using SNI 01-2897-1992 test method for microbiological contamination.Test results showed that drinking water which were treated with ozone concentration below 0.3 ppm still contain Total plate count more than 102 CFU,while those were treated with ozone concentration 0.3 ppm and more comply to requirement for Total plate count according to SNI 01-3551-2006 (Indonesia National Standard for bottled drinking water) for line production where the Total Plate count less than 100 CFU. All untreated samples do not contain salmonella. Test result for Coliform showed that all treated samples have coliform less then 2 colonies. This mean that all treated samples comply to the requirement of to SNI 03-3551-2006 (Indonesia National Standard for bottled drinking water) for Coliform and salmonella.Keywords: The bottled drinking water, ozone, SK 705/MPP/Kep/2003, disinfection AbstrakPenelitian ini bertujuan untuk mendapatkan konsentrasi ozon yang optimum pada proses disinfeksi air minum dalam kemasan. Percobaan dilakukan pada dua pabrik air minum dalam kemasan di Palembang dan Bengkulu. Perlakuan yang diberikan adalah konsentrasi ozon pada tangki pencampur masing masing 0,1 ppm; 0,2 ppm; 0,3 ppm; 0,4 ppm; 0,5 ppm dan 0,6 ppm. Terhadap contoh hasil perlakuan dilakukan pengujian Angka Lempeng Total (ALT), coliform dan Salmonella menggunakan SNI 01-2897-1992 cara Uji Mikroba pada laboratorium terakreditasi. Hasil pengujian menunjukkan bahwa air minum dalam kemasan hasil perlakuan dengan kadar ozon kurang dari 0,3 ppm masih mengandung ALT lebih dari 100 CFU. Sedangkan air minum dalam kemasan hasil perlakuan dengan kadar ozon 0,3 ppm atau lebih memenuhi persyaratan ALT menurut SNI 01-3553-2006 untuk lini produksi, dimana ALT <100 CFU. Semua contoh air baku tidak mengandung Salmonella. Hasil pengujian terhadap Coliform menunjukkan bahwa semua contoh hasil perlakuan mengandung coliform < 2 koloni. Ini berarti bahwa semua contoh hasil perlakuan memenuhi persyaratan SNI 01-3553-2006 untuk coliform dan salmonella.Kata Kunci: Air Minum Dalam Kemasan, Ozon, SK 705/MPP/Kep/2003, Disinfeksi